KECERNAAN BAHAN KERING DAN BAHAN ORGANIK RANSUM YANG MENGANDUNG PELEPAH DAUN KELAPA SAWIT DENGAN PERLAKUAN FISIK, KIMIA, BIOLOGI DAN KOMBINASINYA PADA DOMBA - thomas jekin pindonta (Jurnal Peternakan Integratif, 2014)
ABSTRACT THOMAS JEKIN PINDONTA SURBAKTI, 2014. Dry matter and organic matter digestibility of oil palm frond treated by physical, chemical, biological and their combination on sheep, under supervised by MA’RUF TAFSIN and ARMYN HAKIM DAULAY. The research was conducted at Livestock Biology Laboratory at Department of Animal Husbandry, Agriculture Faculty,University of Sumatra Utara. The research started from June to August 2013 using completely randomize designs, with four treatments and four replications. Sixteen growing local sheep with initial body weight 10 ± 1,16 kg were used in this experiment. The experiment were: P0 (concentrate + oil palm frond be treated a physical); P1 (concentrate + oil palm frond be treated a biological); P2 (concentrate + oil palm frond be treated a chemical); and P3 (concentrate + oil palm frond be treated a combination). The variables were measured consist of dry matter intake and organic matter intake, dry matter digestibility and organic matter digestibility. The result of this research showed that digestibility of oil palm frond treated by, chemical, biological and combination on sheep were significantly higher on dry matter intake, organic matter intake, dry matter digestibility than physical treatment. However, the treatmens were not significantly different (P > 0.05) on organic matter digestibility. It is concluded that treatment of biological, chemical and combination (biology + chemical) had positive effect on dry matter digestibility on sheep but not on phisical treatment. However analisis for organic matter digestibility doesn’t showed giving influence for every treatment. Key word: Oil palm frond, physical, chemical, biological, digestibility, sheep.